The Effect of Saccharomyces cerevisiae Inoculum Concentration On Bioetanol Production From Cocoa Peel (Theobroma cacao L) - Hidayah, Thauhidayatul (LPPM Universitas Qamarul Huda Badaruddin, 2018)
This study aims to determine the effect of S. cerevisiae inoculum concentration on the ethanol content produced in the fermentation process of cocoa pods. The study design used a completely randomized design (CRD). Parameters observed were alcohol content, reducing sugar content and pH. The research was carried out in the laboratory scale and pilot scale. The laboratory scale consists of preliminary and major research. Preliminary research aims to find the optimum concentration of H2SO4 to produce the highest reducing sugar. The main research phase, namely hydrolysis using optimum H2SO4 from preliminary research and fermentation using S. cerevisiae inoculum with variations in inoculum concentrations of 0%, 1%, 3%, 5% and 7% (v / v). The aim of The pilot scale is producing bioethanol. Fermentation was carried out for six days at a temperature of 28-300 C, observations carried out every two days. Measurement of alcohol content using the titration method, reducing sugar content by the Somogyi-Nelson method, and the pH measured by the indicator pH. Pilot scale measurements were carried out by distillation and GC-MS test. Average alcohol content, reducing sugar content, and pH were 23.73%, 90.20 µg / ml, and 4.4. From the pilot scale distillation results, 87.6 ml of distillate were obtained from 1L of cocoa pods substrate. GC-MS test results showed that in distillate ethanol contained 74.944%. The results confirmed that cocoa pods have the potential as bioethanol raw materials. Keywords: Bioethanol, Somogyi-Nelson, Saccharomyces cerevisiae, H2SO4